Practice enhancements with FastStroke ColorViz analysis in acute ischemic stroke - Pai,Vivek; Ti,Joanna Pearly; Tan,Leanne Qiaojing; Ho,Thye Sin; Tham,Carol; Sitoh,Yih Yian (Journal of Clinical Imaging Science)
In acute ischemic stroke (AIS), large vessel occlusion (LVO) and the status of pial collaterals are important factors in decision-making for further treatment such as endovascular therapy. Multiphasic CT Angiogram (mCTA) is the mainstay of AIS imaging, allowing detection of LVO, evaluation of intracranial arterial dynamics, and quantification of pial collaterals. However, thorough mCTA evaluation entails scrutiny of multiple image datasets, individually and then simultaneously, which can be time-consuming, causing a potential delay in treatment. ColorViz (FastStroke, GE Healthcare, Milwaukee, Wisconsin) is a novel CT application which combines mCTA information into a single color-coded dataset for quick, unequivocal evaluation of pial collaterals. In our practice, ColorViz is both time-saving and increases the diagnostic accuracy of LVO and pial collaterals as well as medium vessel, multivessel and posterior circulation occlusions. In this article, we discuss the practical aspects of ColorViz in patients presenting with AIS.